Strategi Pembelajaran Bahasa Arab Di Asrama Darul-Lughoh Al-Arabiyah Pondok Pesantren Darussalam Blokagung Banyuwangi - Mahbub Mahbub; Jauharotut Tauhidiyah (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2022)
The objectives set in this research were to determine the Arabic learning strategy of the Darul-Lughoh Al-Arabiyah Dormitory of Darussalam Islamic Boarding School Blokagung Banyuwangi. This research method uses descriptive qualitative method, data collection through interviews, observation and documentation. The results of this study indicate that the Arabic language learning strategy in Darul Lughoh Al-Arabiyah Islamic Boarding School Darussalam Blokagung Banyuwangi uses a strategy by adjusting each level. This is so that learning strategies for learning Arabic can improve students' abilities in vocabulary, listening, speaking, reading, and writing skills. Thus, this strategy is considered effective and able to improve Arabic language skills. The factors that can improve the Arabic learning strategy of Darul-Lughoh Al-Arabiyah Boarding School Darussalam Islamic Boarding School Blokagung Banyuwangi include: reading books on friday night, ta'lim khorijiy, telling story, mc and public speaking in daily activities, the creativity of the cleric in conveying the material, and the availability of books as learning resources.